Effect of furfuryl alcohol on the properties of hydrated cement mortar - Singh V.K.; Singh R.K.; Khatri S.D. (My University, 2025)
The effect of furfuryl alcohol addition to ordinary cement on its properties, such as heat of hydration, setting time, compressive strength, and tensile strength was studied by adding 0.5-3.0% by weight of cement. Hardness was tested using the Vickers indentation method. Fracture toughness of cementitious bond and bending strength were determined using the three-point bending system. Corrosion resistance of resulting products was tested against 0.1 and 1.0 N HCI and H2SO4 and seawater, respectively. Water absorption/open porosity and microstructure were also determined. It was observed that strength, hardness, toughness, and corrosion resistance increase up to 3.0% addition of furfuryl alcohol in ordinary Portland cement. Polymeric phase was interspersed in cement, causing a decrease in water absorption/open porosity, and its interaction with hydrating cement caused additional bond formation, leading to the increase in strength.